Farmers’ Practices in Developing Agricultural Land in Malaysia: Is there an Islamic Microfinance Solution? - Muhammad Hakimi; Amira Ajeerah (Tazkia Islamic Finance and Business Review, 2013)
Objective – This paper attempts to highlight the farmers’ lives in Malaysia and their problems in developing idle agricultural land.Methods - This paper is using descriptive and exploratory method of study which refer to the situation of agricultural sector in Malaysia.Results - The scheme aPLS (agricultural production and loss sharing) that proposed cannot stand alone in the traditional fiqh to be implemented now. Therefore, the combinations of aPLS contract with ujrah principle are really needed. This is important to ensure the flexibility of the contract that can offer a fully comprehensive scheme of Islamic agricultural finance.Conclusion – The land together with labour can be considered as a form of capital and therefore has a similarity to the contracts of mudaraba and musharaka. Hence, it can be said that these principles are “agricultural production and loss sharing (aPLS)” because land will naturally produce an output or a product. Muzara’a and musaqa therefore can be said to be contracts which are based on sharing output rather than sharing profit.Keywords: Idle Agricultural Land, Islamic agricultural finance, Malaysia